The Predictors Of Religiosity Towards Leadership In Education - AZIZI, MOHD NAZRUL; ISHAK, ZAHARI; HILMI, FIRDAUS (The journal of contemporary issues in business and government, 2021)
The current study investigates the influence of religiosity and Emotional Intelligent on the attitude towards leadership in education. Data were collected from undergraduate students who constitute future leaders. Results from the regression analysis particularly the relative weight analysis, revealed that leadership practices demonstrated significant incremental variance with attitude towards leadership beyond the self- leadership. The implications of the findings for research and practice are discussed.